2017
DOI: 10.2147/ceor.s134230
|View full text |Cite
|
Sign up to set email alerts
|

Oncology drugs for orphan indications: how are HTA processes evolving for this specific drug category?

Abstract: Orphan drugs (ODs) are intended for the diagnosis, prevention, or treatment of rare diseases. Many cancer subtypes, including all childhood cancers, are defined as rare diseases, and over one-third of ODs are now intended to treat oncology indications. However, market access for oncology ODs is becoming increasingly challenging; ODs are prone to significant uncertainty around their cost-effectiveness, while payers must balance the need for these vital innovations with growing sensitivity to rising costs. The o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
21
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 26 publications
0
21
0
Order By: Relevance
“…Data for between 2005 and 2011 for TLV decisions on the inclusion of drugs in the pharmaceutical benefits scheme show that the lowest cost per QALY declined was 700,000 SEK while the highest accepted was 1,220,000 SEK [35]. This compares favourably also to oncology drugs that have been assessed positively by the Swedish council for novel therapeutics with ICERs per QALY up to 1,080,000 SEK (with pertuzumab being the exemption, having an ICER at 2,600,000 SEK) [36].…”
Section: Discussionmentioning
confidence: 99%
“…Data for between 2005 and 2011 for TLV decisions on the inclusion of drugs in the pharmaceutical benefits scheme show that the lowest cost per QALY declined was 700,000 SEK while the highest accepted was 1,220,000 SEK [35]. This compares favourably also to oncology drugs that have been assessed positively by the Swedish council for novel therapeutics with ICERs per QALY up to 1,080,000 SEK (with pertuzumab being the exemption, having an ICER at 2,600,000 SEK) [36].…”
Section: Discussionmentioning
confidence: 99%
“…Although the rarity of the disease is one of the variables that are normally mentioned in the literature to consider higher than usual thresholds, Adkins et al did not identify country-specific guidance and health technology assessment (HTA) documentation for recently evaluated ODs. 80 None of these countries were found to have explicit HTA criteria for the assessment of ODs; therefore, ODs are assessed through the usual HTA process. As far as we know, only the National Institute for Health and Care Excellence seems to consider a higher threshold linked to the NICE's Highly Specialised Technologies Programme.…”
Section: Discussionmentioning
confidence: 99%
“…Adkins et al ( 2017 ) made a review to evaluate different mechanisms that have been introduced to facilitate patient access to oncologic orphan drugs in 5 different countries (Australia, Canada, England, France, and Sweden), using 8 oncologic orphan drugs and non-orphan oncologic drugs as examples of their application. It was revealed that additional assessment processes were rarely used and decisions were mostly driven by proving cost-effectiveness using standard incremental cost-effectiveness ratio thresholds.…”
Section: Discussionmentioning
confidence: 99%